Unexplained groin pain: safety and reliability of herniography for the diagnosis of occult hernias. Issue 906 (1st April 2001) - Gwanmesia, I I; Walsh, S; Bury, R; Bowyer, K; Walker, S
Abstract : A retrospective study of our initial experience of herniography in a district general hospital is presented. A total of 43 herniograms were performed in 41 patients (median age 57, range 16–77, 27 males, 14 females) over a two year period. Four herniograms were unsuccessful due to failed intraperitoneal contrast injection, of which two were repeated (success rate 90.5%). A total of 25 groin hernias were identified radiologically (two on the asymptomatic side). Twenty one patients underwent surgery and a hernia was confirmed in 19 (true positive rate 90.5%). Sixteen herniograms were considered negative and after a median follow up of 28 months (range 16–42 months), none of these patients have developed a hernia. There were no major complications. It is concluded that herniography is a safe and reliable method of determining or excluding the presence of an occult groin hernia.